Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ejmp.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging dose from cone beam computed tomography in radiation therapy

Abstract: Imaging dose in radiation therapy has traditionally been ignored due to its low magnitude and frequency in comparison to therapeutic dose used to treat patients. The advent of modern, volumetric, imaging modalities, often as an integral part of linear accelerators, has facilitated the implementation of image-guided radiation therapy (IGRT), which is often accomplished by daily imaging of patients. Daily imaging results in additional dose delivered to patient that warrants new attention be given to imaging dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 91 publications
4
86
0
Order By: Relevance
“…Fractionated radiation treatments are usually delivered in 20 fractions to improve patient tolerance, so the total radiation dose from CBCT is a factor of 20 greater than that of a single scan 18. Besides, CBCT doses are distributed to the entire imaging region, not only the target volume 19. Hence, it is necessary to know what the radiation doses are from CBCT and raise awareness of using lower radiation doses.…”
Section: Introductionmentioning
confidence: 99%
“…Fractionated radiation treatments are usually delivered in 20 fractions to improve patient tolerance, so the total radiation dose from CBCT is a factor of 20 greater than that of a single scan 18. Besides, CBCT doses are distributed to the entire imaging region, not only the target volume 19. Hence, it is necessary to know what the radiation doses are from CBCT and raise awareness of using lower radiation doses.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of dual-energy capabilities in CBCT units is finding application in diagnostics to improve material segmentation and enhance contrast. A model of the kV CBCT unit is required to optimize the imaging device, to simulate and correct for scatter radiations, 1 to optimize single 2 and dual-energy acquisition protocols, to compute the patient imaging dose, 3 and for material decomposition in dual-energy CT.…”
Section: Introductionmentioning
confidence: 99%
“…Verification of CBCT models has been carried out in different manners in the literature. 3 To validate the x-ray source model, some authors performed half-value layer (HVL) measurements, 1,4 but only the first HVL is commonly checked. In a recent work, 5 the authors proposed an original experimental setup to rapidly characterize x-ray sources by acquiring angular-dependent HVLs and fluence data.…”
Section: Introductionmentioning
confidence: 99%
“…The few other studies to be found that calculated the imaging dose on the planning CT did not systematically evaluate different IGRT scenarios but focussed on kV modalities [1821]. Alaei et al [20] showed that the dose from daily kV CBCT results in an additional isocenter dose of the order of 30–40 mGy for 35 fractions head and neck and 230–240 mGy for 25 fractions pelvis irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly indebted to the fact that imaging energies are not usually commissioned in the treatment planning system (TPS) and not included in the treatment plan. A few studies have calculated the imaging dose for each patient on the planning CT [1721], but a systematic evaluation of different imaging scenarios on treatment plan quality is still missing. Furthermore, biological effects have been generally disregarded.…”
Section: Introductionmentioning
confidence: 99%